1 - Thinking otherwise: theorizing the colonial/ modern gender system in Africa. - Boris Bertolt, (African Sociological Review, 2018)
This article aims to show that there is an entanglement between representations of the body and gender inequalities between the colonial period and contemporary African societies. Postcolonial Africa remains deeply marked by representations of sex, body and gender during colonization. This epistemological stance has the consequence of denying the idea of the end of decolonization, which appears at this moment as a myth. It derives theoretically from the works of the Latin American modernity / coloniality research program. Coloniality is understood as a set of paradigms of domination and regulation of the life of the colonized introduced during the construction of European hegemony around the world since the fifteenth century. Contemporary Discourses and knowledge about gender dynamics remain deeply embedded in Eurocentric thinking. To illustrate this situation, two aspects of life of former colonized seemed to me important to highlight: the inferiorization of women in Africa and gender categories. Even if it is not my point to argue that the situation of women and gays in Africa was better before contacts with Europeans, I am trying to show that the subalternization of women and homosexuals in contemporary Africa can’t be account without a deep surgery on the body of colonized people and speeches about sexuality.